2014
DOI: 10.1186/1748-5908-9-51
|View full text |Cite|
|
Sign up to set email alerts
|

Towards a common terminology: a simplified framework of interventions to promote and integrate evidence into health practices, systems, and policies

Abstract: BackgroundA wide range of diverse and inconsistent terminology exists in the field of knowledge translation. This limits the conduct of evidence syntheses, impedes communication and collaboration, and undermines knowledge translation of research findings in diverse settings. Improving uniformity of terminology could help address these challenges. In 2012, we convened an international working group to explore the idea of developing a common terminology and an overarching framework for knowledge translation inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
149
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(149 citation statements)
references
References 30 publications
0
149
0
Order By: Relevance
“…In health care, recent reviews of these 1,16,[18][19][20][21] have identified the diverse languages used to describe new models -such as knowledge translation, knowledge exchange, knowledge interaction, knowledge intermediation and knowledge mobilisation. 22,23 These reviews have also begun to map out the empirical support for various mechanisms thought to promote effective knowledge sharing.…”
Section: Framing the Problemmentioning
confidence: 99%
“…In health care, recent reviews of these 1,16,[18][19][20][21] have identified the diverse languages used to describe new models -such as knowledge translation, knowledge exchange, knowledge interaction, knowledge intermediation and knowledge mobilisation. 22,23 These reviews have also begun to map out the empirical support for various mechanisms thought to promote effective knowledge sharing.…”
Section: Framing the Problemmentioning
confidence: 99%
“…Implementation science has been the focus of many studies, to the point of leading to a certain confusion of definitions and theoretical frameworks (22,23). Some authors have sought to bring these together in integrative frameworks and clarify the concepts used (9,10,22,23).…”
Section: Implementation Sciencementioning
confidence: 99%
“…Some authors have sought to bring these together in integrative frameworks and clarify the concepts used (9,10,22,23). Despite the efficacy of implementation strategies adapted to identified barriers (11), it remains unknown which implementation interventions are most effective, in what context, with what mechanisms and means of administration (23).…”
Section: Implementation Sciencementioning
confidence: 99%
“…Fidelity scores were also used to help establish the relationship between treatment components and outcomes, a first step toward identifying the Bactive ingredients^of the ASPIRE-VA coaching approach [27]. This will help determine which components can be adapted to other healthcare settings without compromising treatment effectiveness [12].…”
Section: Methodsmentioning
confidence: 99%